The protection of animals in Poland. A legal and social problem - Gardocka, Teresa (НТУ "ХПИ", 2014)
The problem regards relating to the various groups of animals in danger of extinction: domestic animals, animals used during entertainment events (circuses), animals, kept by people usually in order to provide a company and sometimes due to the specific needs (e.g. guide dogs for the blind), livestock, game animals, experimental (laboratory) animals, as well as fish and insects in order to protect a biodiversity, and also for the educational mission addressed primarily to the young people. Legislative, social and religious aspects of a problem are investigated. At present the European law plays an important role in the problem of protection of animals. For instance: the Polish statute is undergoing a process of changes connected to the necessity of implementation of the European Union directive regarding the protection of experimental animals because the internal law of the State members should be in conformity with the European acts. The main idea of the article is based on the statement that an animal is not a thing but a living creature able to feel suffering and the human society must feel and reduce these sufferings. The author stresses that the low level of social acceptance for the requirement of the humanitarian treatment of animals constitutes a problem. Special relevance of the article is a society doesn't understand why one should take care of the animal welfare, does not accept spending money on it and does not show any empathy for animals. Killing of a homeless animal is easily justified socially while a movement in favor of animals, especially among young people, requires a change of the old provisions neglecting the animal rights.

Проблема рассматривается в отношении различных групп животных, находящихся под угрозой вымирания: домашних питомцев, животных, используемых для развлечений (цирк), для специфических нужд (собаки-поводыри), домашнего скота, диких животных, экспериментальных (лабораторных) животных, в том числе рыб и насекомых, с целью сохранения природного биологического разнообразия, а также просвещения молодого поколения. Исследуются законодательные, социальные и религиозные аспекты проблемы. В настоящее время Европейский закон играет важную роль в проблеме защиты животных. Например, Польский устав подвергается ряду изменений в связи с необходимостью внедрения директив Евросоюза относительно защиты экспериментальных животных, поскольку внутригосударственное право должно соответствовать Европейским актам. Главная идея статьи основана на утверждении, что животное – это не вещь, а живое существо, способное испытывать страдания, и человеческое общество должно чувствовать и уменьшать эти страдания. Автор подчеркивает, что низкий уровень принятия социумом требований гуманного обращения с животными создает проблему. Особая актуальность статьи состоит в том, что значительная часть общества не понимает, зачем заботиться о благополучии животных, тратить деньги на их нужды и, вообще, проявлять какое-либо сочувствие. Убийство бездомного животного с легкостью оправдывается социумом, в то врем, как движение в пользу защиты животных, особенно среди молодежи, требует изменения прежних условий, пренебрегающих правами животных.
Защита животных в Польше. Правовая и социальная проблема
Keywords: European Union; domestic animals; livestock; Евросоюз; домашние животные; домашний скот